Nickel-based catalysts for fuel cell anodes

Nickel-molybdenum-rhenium catalysts supported by conductive carbon address the limitations of platinum in alkaline fuel cells by providing a cost-effective and stable anode solution, improving performance and scalability.

JP7624441B2Active Publication Date: 2025-01-30GENCELL LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2022523153
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-10-18
Filing Date
2020-10-15
Publication Date
2025-01-30
Estimated Expiration
2040-10-15

AI Technical Summary

Technical Problem

The high cost and limited global supply of platinum-based catalysts, along with their sensitivity to poisons, hinder the widespread use of alkaline fuel cells, necessitating the development of cost-effective and stable alternatives for the anode catalysts in fuel cells.

Method used

A nickel-based catalyst supported by conductive carbon, modified with transition metals such as molybdenum and rhenium, is used to enhance the electrochemical activity and stability of the anode in alkaline fuel cells, eliminating the need for platinum and other precious metals.

Benefits of technology

The nickel-molybdenum-rhenium catalysts provide a cost-effective and stable alternative to platinum, maintaining high electrochemical activity and reducing sensitivity to poisons, thereby enhancing the performance and scalability of alkaline fuel cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007624441000001
    Figure 0007624441000001
  • Figure 0007624441000002
    Figure 0007624441000002
Patent Text Reader

Abstract

A catalyst suitable for use in the anode of a fuel cell, the catalyst comprising (i) nickel and (ii) molybdenum, and optionally (iii) rhenium and / or (iv) at least one transition metal different from nickel, molybdenum, and rhenium, in at least partially reduced form, supported on (v) conductive carbon modified with one or more elements selected from lanthanides, yttrium, tin, and titanium, wherein the weight ratio (i):((ii)+(iii)+(iv)) is at least 2:1.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] This application claims priority to U.S. Provisional Patent Application No. 62 / 916,837, filed October 18, 2019, the entire disclosure of which is expressly incorporated herein by reference. The present invention relates to a nickel-based catalyst for the anode of a fuel cell, in particular an alkaline fuel cell. The present invention also relates to a process for producing the catalyst and to an anode comprising the catalyst. [Background technology]

[0002] Fuel cells (FCs) are one of the oldest electrochemical devices that generate electricity, heat and water by direct electrochemical reaction of hydrogen-rich fuels with oxygen without any harmful emissions and thus in a very environmentally friendly way. The direct generation of electricity allows for high energy efficiency of FCs. FCs are being deployed as a future alternative power generation technology for both mobile and stationary applications, from toys to large-scale power stations and power plants, from automobiles to mobile chargers, from home power to battlefield power. FCs are generally classified according to the nature of the electrolyte into alkaline fuel cells (AFCs), proton exchange membrane fuel cells (PEMFCs), solid oxide fuel cells (SOFCs), phosphoric acid fuel cells (PACFs) and molten carbonate fuel cells (MCFCs), each with its own unique characteristics and each type requiring specific materials and fuels. However, they all contain the same essential components, namely, anode support, anode catalyst layer, electrolyte, cathode support, cathode catalyst layer, bipolar plates / interconnects, and sometimes gaskets to seal / prevent leakage of gas between the anode and cathode. Each fuel cell type also has its own unique operating characteristics and offers advantages for specific applications, making fuel cells a very versatile technology.

[0003] AFCs are promising environmentally friendly electrochemical power sources for distributed cogeneration in buildings and transportation. Conventional AFCs run on compressed hydrogen and oxygen and typically use a solution of potassium hydroxide in water as the electrolyte. AFCs use a liquid KOH electrolyte solution because it is the most electrically conductive of all the alkaline hydroxides and is also an effective medium for heat transfer and water management. In these cells, hydroxyl ions (OH - ) travels from the cathode to the anode. Hydrogen fuel is continuously fed to the anode compartment, and oxidant (often oxygen from air) is continuously fed to the cathode compartment. At the anode, oxygen gas reacts with water to produce OH - It produces ions and releases electrons. The electrons produced at the anode power an external circuit and then return to the cathode, where they react with oxygen and water to produce further OH. - They generate ions, which diffuse into the electrolyte. AFCs operate at up to 70% efficiency and produce very little pollution. They were a logical choice for spacecraft because they can also produce drinking water in addition to electricity. The voltage between the anode and cathode ranges from 0.5 to 0.9 V, depending on the load and the electrochemical reaction.

[0004] In low- and intermediate-temperature FCs, platinum and platinum group metals alone (Pt / C) or combinations of two or more of them, and their corresponding alloys, are preferred as ideal materials suitable for use as electrocatalysts for both hydrogen oxidation reaction (HOR) and oxygen reduction reaction (ORR) due to their high capacity and performance in all media. However, the cost and limited global supply of Pt are significant barriers to the widespread use of these types of fuel cells. Thus, large-scale production and application of precious metal catalysts in practical FCs is limited due to scarce global resources and high cost.

[0005] Attempts have been made to partially or completely replace platinum as the anode of AFCs by transition metal compositions that retain the performance of fuel cell electrodes without being too expensive. Apart from their lower cost, another advantage of transition metal catalysts is their low susceptibility to poisoning.

[0006] Palladium is the most attractive alternative to platinum because these two metals have very similar properties (same group in the periodic table, same fcc crystal structure, similar atomic size, etc.). In the past (but not currently), the cost of palladium was lower than that of platinum. Palladium is at least 50 times more abundant on Earth than platinum. For these reasons, palladium has been tested in fuel cells as a promoter for platinum in alkaline media and / or as a platinum-free anode catalyst. The addition of metals such as Co, Ru, Mn and especially Ni has been reported to significantly promote the activity and stability of Pd / C electrocatalysts.

[0007] Various inexpensive non-precious metal materials (e.g., Fe, Co, and Ni) have also been used as fuel cell components. The catalytic activity of nickel as an anode catalyst is about three orders of magnitude lower than that of platinum. This performance deficiency can be remedied to some extent by significantly increasing the loading of inexpensive catalysts on the electrode, either by enlarging the active area using finely divided particles or by otherwise optimizing the electrode structure. In this regard, nickel-containing composites such as nickel boride (Ni2B) have been widely used as anode materials because nickel metal is highly conductive, resistant to corrosion by potassium hydroxide, and exhibits unique catalytic activity for hydrogen oxidation reaction (HOR). Among the non-precious metals most active for HOR, Raney-nickel catalysts have been of interest, especially in AFCs. However, electrodes with unsupported Raney-nickel catalysts have been reported to have the weakness of insufficient electrical conductivity. Therefore, to promote the electrical conductivity of the catalyst layer and enhance the catalytic activity, Raney-nickel catalysts have been alloyed with carbon materials. Raney nickel-hydrogen electrodes containing nickel alone as the transition metal component exhibit relatively large polarization, time-dependent behavior and high electrolyte diffusion resistance due to low pore volume and small pore diameter. These problems have been circumvented by doping the starting Ni-Al alloy with small proportions of transition metals such as Ti, Cr, Fe and Mo before extraction with KOH. Aiming to overcome the above mentioned difficulties, other preparation methods of active metals, with or without metal dopants (Ti, Mo, Fe, Cr, Cu), have been proposed and reported in the literature.

[0008] Metal hydride (MH) alloys, MmNi 3.5 Co 0.7 Al 0.7 Mn 0.1 and MlNi 3.65 Co 0.85 Al 0.3 Mn 0.3Intermetallic compounds such as (Ml:La-rich misch metal) have also been tested for use as anode catalysts in AFCs. They are characterized by good electrochemical properties, mechanical and chemical stability in alkaline electrolytes.

[0009] According to recent published papers and patents, nickel-containing catalysts continue to be applied as the most promising material for the preparation of anode electrodes for H2-O2 AFCs. In some AFCs, the anode catalyst material consists of 65% nickel and 35% aluminum, with 1% carbon black and 7% PTFE as binders (see, for example, JP 2007-087924, the disclosure of which is incorporated herein in its entirety). In other AFCs, the electrode is obtained by applying a catalyst supporting Ni, Co and Fe on carbon particulates to the surface of nickel foam. PTFE is used as a binder (see, for example, US 2009 / 0004521, the disclosure of which is incorporated herein in its entirety). In yet another AFC, the anode catalyst layer contains nickel and the cathode catalyst layer contains silver. Also, the CO2 inhibitor of the present invention is in the form of a polymer-bound CO2 adsorbent. In particular, the catalytic layer of the anode electrode promotes desorption of CO2 (see, e.g., U.S. Patent Application Publication No. 2010 / 0239921, the disclosure of which is incorporated herein in its entirety).

[0010] In view of the above, it would be advantageous to be able to replace the platinum metal used in the preparation of the anode electrocatalyst with a non-platinum metal, such as a transition d metal, without significantly decreasing the electrochemical activity of the catalyst. Summary of the Invention

[0011] The present invention provides a catalyst suitable for use in the anode of a fuel cell, in particular an alkaline fuel cell. The catalyst comprises (i) nickel and (ii) molybdenum, and optionally present elements (iii) rhenium and / or (iv) at least one transition metal different from nickel, molybdenum and rhenium, in at least partially reduced (metallic) form. The weight ratio (i):((ii)+(iii)+(iV)) is at least 2:1. Components (i), (ii) and optionally (iii) and / or (iv) are supported on (v) conductive carbon modified with one or more elements selected from the lanthanides, yttrium, tin and titanium (e.g. in the form of TiO2).

[0012] In one embodiment of the catalyst, component (iii) may be present. In another embodiment, component (iv) may be present. In yet another embodiment, components (iii) and (iv) may be present. Component (iv) may include, for example, one or both of cobalt and tungsten.

[0013] In another embodiment, the conductive carbon may be modified with one or more lanthanides selected from cerium and lanthanum, and / or with yttrium, and / or with tin, preferably in a partially or substantially fully oxidized form (i.e., in the form of an oxide). Cerium is preferred as the modifying element. For example, the one or more elements modifying the conductive carbon may be present in a (total) concentration of at least 0.5% by weight, calculated as pure metal, based on the total weight of the modified conductive carbon.

[0014] In another embodiment of the catalyst of the present invention, the catalyst may comprise at least 10 wt. % of component (i), and / or at least 0.5 wt. % to no more than 5 wt. % of component (ii), and / or at least 0.5 wt. % to no more than 5 wt. % of component (iii), and / or at least 0.5 wt. % to no more than 5 wt. % of component (iv), based on the total weight of components (i)-(v).

[0015] In yet another embodiment, the catalyst of the present invention may be substantially free of Pt, in particular substantially free of Pt, Ru, Rh, Ag and Au (preferably also free of Pd, Ir and Os). In another embodiment, the catalyst may (also) be substantially free of Al, and preferably substantially free of other main group metals (except yttrium and tin).

[0016] In another embodiment of the catalyst of the present invention, the support (v) has a thickness of at least 50 m 2 / g and / or at least 50% of the particles may have a particle size of 30 μm or less.

[0017] In another embodiment, the catalyst of the invention may be obtained by a process comprising impregnating component (v) with a solution of one or more compounds of nickel and molybdenum, with a solution of one or more compounds of optional rhenium and / or with one or more solutions of one or more compounds of nickel, molybdenum and one or more compounds of a transition metal different from rhenium, followed by at least partial reduction of the metals present.

[0018] The present invention further provides an anode for a fuel cell, preferably an alkaline fuel cell, which comprises the above-described catalyst of the present invention, including its various embodiments, and a fuel cell comprising this anode.

[0019] The present invention further provides a process for the preparation of the catalyst of the invention as described above, which comprises impregnating component (v) with a solution of one or more compounds of nickel and molybdenum, and optionally one or more compounds of rhenium and / or one or more compounds of nickel, molybdenum and one or more compounds of a transition metal different from rhenium, followed by at least partial (preferably substantially complete) reduction of the impregnating metals present.

[0020] In one embodiment of the process, the impregnation (or impregnation with at least one of the solutions used) may be carried out by the incipient wetness method.

[0021] In yet another embodiment of the process, the reduction may be preceded by a drying operation and optionally a calcination operation.

[0022] In yet another embodiment of the process, the at least partial reduction may be carried out with hydrogen, preferably in the presence of urea.

[0023] The present invention further provides a process for making an anode suitable for use in a fuel cell. The process includes mixing the catalyst of the present invention described above (including various aspects thereof) with a binder, forming the resulting mixture into a ribbon (e.g., by rolling), and then combining the ribbon (usually under pressure) with a current collector (e.g., by pressing) to form the anode material (which may be cut into pieces of desired dimensions for the anode). The binder may include, for example, polytetrafluoroethylene. The current collector may include, for example, a metal grid, such as a nickel grid.

[0024] The present invention further provides an electrical device in connection with a fuel cell according to the present invention as described above, and a method of powering an electrical device, the method comprising establishing an electrical connection between a device as described above and a fuel cell according to the present invention as described above. [Brief description of the drawings]

[0025] The invention is further explained in the following detailed description with reference to the accompanying drawings, which show non-limiting examples of exemplary embodiments of the invention. [Figure 1] FIG. 1 shows a graph of current density versus applied potential on a half-cell test bench using an electrocatalyst obtained as described in Examples 1 and 2 below. [Diagram 2]FIG. 2 shows a graph of current density versus applied potential on a half-cell test bench using an electrocatalyst obtained as described in Example 3 below. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0026] The details shown in this specification are exemplary and are presented only for the purpose of discussion illustrating embodiments of the present invention, and are presented to provide what is believed to be the most useful and easily understood explanation of the principles and conceptual aspects of the present invention. In this regard, no attempt has been made to show the structural details of the present invention in more detail than is necessary for a fundamental understanding of the present invention, and the description made with the drawings will make clear to those skilled in the art how some forms of the present invention can be actually implemented.

[0027] As used herein, the singular forms "a," "an," and "the" include plural referents unless the context clearly dictates otherwise. For example, reference to a "transition metal" means that a mixture of two or more transition metals may be present unless specifically excluded.

[0028] Unless otherwise indicated, all numerical values ​​expressing quantities of ingredients, reaction conditions, and so forth used in the specification and appended claims are to be understood as being modified in all instances by the term "about." Accordingly, unless otherwise indicated, the numerical parameters set forth in the specification and appended claims are approximations that may vary depending upon the desired properties sought to be obtained by the present invention. At the very least, each numerical parameter should be construed in light of the number of significant digits and ordinary rounding approaches.

[0029] Additionally, disclosure of a numerical range within this specification is considered to be a disclosure of all numerical values ​​and ranges within that range. For example, if a range is 1 to 50, it is considered to include, for example, 1, 7, 34, 46.1, 23.7, or any other value or range within the range.

[0030] The catalyst of the present invention comprises nickel and molybdenum, and optionally rhenium and / or one or more (e.g. 1, 2 or 3) transition metals different from nickel, molybdenum and rhenium, at least in partial (preferably substantially completely reduced = metallic) form. Examples of suitable transition metals include Y, Ti, Zr, Hf, V, Nb, Ta, Cr, Mo, W, Mn, Fe, Co, Cu, Zn, Cd. Preferred transition metals are Co and W. It is particularly preferred that Re is additionally present. It is also preferred that the catalyst is substantially free of Pt. It is even more preferred that the catalyst is substantially free of Pt, Pd, Ru, Rh, Ag, Au. For example, the catalyst may be substantially free of Pt, Ru, Rh, Ag, Au, Pd, Os, Ir. It is also preferred that the catalyst is substantially free of Al or other main group metals different from yttrium and tin (the latter metals may be present on the carbon support). The term "substantially free" as used herein and in the appended claims is intended to mean that 0.1 wt. % or less, e.g., 0.05 wt. % or less, 0.01 wt. % or less, or 0.001 wt. % or less of the corresponding metal is present in the catalyst, based on the total weight of the metal and conductive carrier present in the catalyst of the invention. It is also preferred that the catalyst of the invention consists essentially of or consists of components (i), (ii) and (v), components (i), (ii), (iii) and (v), components (i), (ii), (iv) and (v), or components (i), (ii), (iii), (iv) and (iv).

[0031] The weight ratio of component (i):component ((ii)+(iii)+(iv)) is preferably at least 2.5:1, e.g., at least 3:1, at least 3.5:1, or at least 4:1, based on pure metals, regardless of whether components (iii) and / or (iv) are present. This weight ratio is typically 20:1 or less, e.g., 15:1 or less, 10:1 or less, or 8:1 or less.

[0032] Based on the total weight of components (i) to (v), the catalyst of the invention preferably comprises at least 10 wt.-%, for example at least 12 wt.-%, at least 15 wt.-%, at least 18 wt.-% or at least 20 wt.-% nickel, calculated as pure metal. The concentration of nickel will usually not exceed 30 wt.-%, although higher concentrations (usually up to 50 wt.-%) are possible.

[0033] Based on the total weight of components (i) to (v), the catalyst of the invention preferably comprises at least 0.5 wt.-%, for example at least 1 wt.-%, at least 1.5 wt.-%, at least 2 wt.-%, or at least 2.5 wt.-%, of molybdenum, calculated as pure metal. The concentration of molybdenum will usually not exceed 5 wt.-%, although higher concentrations are possible.

[0034] When component (iii) is present, the catalyst of the invention preferably comprises at least 0.5 wt.-%, for example at least 1 wt.-%, at least 1.5 wt.-%, at least 2 wt.-%, or at least 2.5 wt.-%, of rhenium, calculated as pure metal, based on the total weight of components (i)-(v). The concentration of rhenium will usually not exceed 5 wt.-%, although higher concentrations are possible.

[0035] When component (iv) is present, the catalyst of the invention preferably comprises a total of at least 0.5 wt.-%, for example at least 1 wt.-%, at least 1.5 wt.-%, at least 2 wt.-% or at least 2.5 wt.-%, calculated as pure metal, based on the total weight of components (i)-(v). The total concentration of these transition metals will usually not exceed 5 wt.-%, although higher concentrations are possible.

[0036] Based on the total weight of components (i)-(v), the catalyst of the invention preferably comprises at least 50 wt.%, e.g., at least 55 wt.%, at least 60 wt.%, at least 65 wt.%, or at least 70 wt.% of component (v), although higher and lower concentrations than those stated are possible. The one or more elements modifying the conductive carbon are typically present in an (overall) concentration of at least 0.5 wt.%, e.g., at least 1 wt.%, or at least 2 wt.%, but preferably no more than 20 wt.%, e.g., no more than 15 wt.%, no more than 10 wt.%, or no more than 5 wt.%, calculated as pure metal, based on the total weight of the modified conductive carbon.

[0037] The support of the catalyst of the present invention is at least 50 m 2 / g, e.g., at least 100m 2 / g, at least 200m 2 / g or at least 300m 2 It is preferable that the support has a specific surface area of ​​100 / g (measured by the BET method using nitrogen gas). There is no particular upper limit to the specific surface area, but as the specific surface area of ​​the support increases, it is obviously more difficult to handle the support.

[0038] The support typically has a particle size (applying to at least 90% of all particles) of about 0.5 μm or more, e.g., about 1 μm or more, about 5 μm or more, or about 10 μm or more, and about 100 μm or less, e.g., about 80 μm or less, or about 70 μm or less. It is preferred that at least 50% of the support particles have a particle size of 30 μm or less, e.g., 25 μm or less, or 20 μm or less. Conductive carbon materials suitable for the purposes of the present invention are available from a number of commercial sources. Non-limiting examples of suitable commercially available products are those under the trade names Vulcan XC-72, Vulcan P90, Black Pearls 2000, Black Pearls 450, Black Pearls 570, Regal 400, Regal 330 (all available from Cabot, USA), Picatif SC 10 (available from Pica USA Inc, Columbus, Ohio), Norit GSX, Norit SX Plus, Norit DLC Supra (available from Norit, Netherlands), carbon AKC, HSAG-300CAT (available from Lonza, Switzerland), and Sibunit (available from the Institute of Technical Carbon, Omsk, Russia; see also U.S. Pat. No. 4,978,649, the entire disclosure of which is incorporated herein by reference).

[0039] The catalyst of the present invention can be prepared by many different methods known to those skilled in the art. According to a preferred method, the support (v) is impregnated by contacting it with a (preferably aqueous or aqueous / alcoholic) solution of the corresponding metal compound (usually in the form of metal salts of inorganic acids such as nitrates and halides or, in particular in the case of molybdenum and rhenium, complex salts such as rhenates and molybdates such as ammonium molybdate and ammonium rhenate). Preferably, the impregnation is carried out by the incipient wetness method, which is usually followed by drying and optionally calcination. Drying may be carried out at a temperature in the range of, for example, 60° C. to 120° C., while calcination is usually carried out at a temperature in the range of, for example, 200° C. to 400° C. The dried and optionally calcined support is then subjected to reduction. A preferred reducing agent is hydrogen gas (usually diluted with an inert gas such as nitrogen). In this case, the reduction is usually carried out at elevated temperatures (for example in the temperature range of 400° C. to 600° C.). The reduction with hydrogen gas is preferably carried out in the presence of urea. The preferred weight ratio of impregnating metal (Ni+Mo+any metal):urea is 1:1 to 1:4, for example 1:1.5 to 1:2.5.

[0040] Anodes for fuel cells can be fabricated from the nickel-containing catalyst of the present invention by conventional methods known to those skilled in the art. By way of example only, a material comprising the catalyst of the present invention and a binder (e.g., PTFE) can be wound into a ribbon. The ribbon can be pressed onto a current collector such as a metal (e.g., nickel) grid.

[0041] The material comprising the Ni-based catalyst of the present invention may be used as the anode of a fuel cell, in particular an alkaline fuel cell. The cathode of the fuel cell may be any cathode that may be used in combination with an (alkaline) fuel cell, examples of which are well known to those skilled in the art.

[0042] A typical fuel cell structure according to the invention, in its operating condition, includes an anode in contact with a fuel (e.g., hydrogen gas) on one side and a liquid electrolyte (e.g., an aqueous alkali metal hydroxide, preferably aqueous KOH) on the other side, and a cathode in contact with the liquid electrolyte on its one side, the other side of the cathode being in contact with an oxidant, preferably oxygen, air or other oxygen-containing gas.

[0043] The fuel cells of the present invention may be used to supply electrical energy to a virtually unlimited number of electrical and electronic devices.

[0044] Working Example Example 1 Synthesis of 50g of catalyst 27.0%Ni-3.0%Mo-70.0% support (CeO2 modified carbon) solution 1 66.906 g of Ni(NO3)2·6H2O was placed in a glass beaker and dissolved in 50 ml of deionized water under vigorous stirring with a magnetic stirrer without heating until completely dissolved.

[0045] solution 2 2.762g of (NH4)6Mo7O 24 ·4H2O was placed in a glass beaker and dissolved in 50 ml of deionized water with vigorous stirring using a magnetic stirrer without heating until completely dissolved.

[0046] Solutions 1 and 2 were mixed and diluted to 150 ml with deionized water and stirred to obtain a homogenous solution.

[0047] Impregnation of the modified support with Ni-Mo mixed solution was carried out according to the incipient wetness method by stepwise impregnation followed by drying at 105 C. After the final impregnation, the sample was calcined at 300 C for 120 min and subsequently reduced with hydrogen (5–10% H2 in N2) in the presence of urea (mass ratio (Ni+Mo) / urea=1 / 2) at 520 C for 180 min.

[0048] The modification of conductive carbon (S88) with CeO2 was carried out according to the procedure disclosed in Hamish A. Miller et al., Nano Energy 33 (2017) pp. 293-305, the entire disclosure of which is expressly incorporated herein by reference.

[0049] Example 2 Synthesis of 25g of catalyst 27.0%Ni-3.0%Mo-2.5%Re-67.5% support (CeO2 modified carbon) solution 1 33.4502 g of Ni(NO3)2·6H2O was placed in a glass beaker and dissolved in 40 ml of deionized water under vigorous stirring with a magnetic stirrer without heating until completely dissolved.

[0050] solution 2 1.3805g of (NH4)6Mo7O 24 ·4H2O was placed in a glass beaker and dissolved in 25 ml of deionized water with vigorous stirring using a magnetic stirrer without heating until completely dissolved.

[0051] Solutions 1 and 2 were mixed and diluted to 100 ml with deionized water and stirred to obtain a homogenous solution.

[0052] solution 3 0.9012 g of NH4ReO4 was placed in a glass beaker and dissolved in 50 ml of deionized water under vigorous stirring with a magnetic stirrer without heating until completely dissolved.

[0053] Impregnation of the modified support with Ni-Mo mixed solution was carried out according to the incipient wetness method by stepwise impregnation followed by drying at 105 °C. After the last impregnation, the sample was calcined at 300 °C for 120 min and subsequently impregnated with solution 3. The thus impregnated sample was dried overnight at 105 °C and then reduced with hydrogen (5-10% H2 in N2) at 520 °C for 180 min.

[0054] The modified conductive carbon was the same as in Example 1 above.

[0055] Example 3 Synthesis of 25g of catalyst 22.5%Ni-2.5%Mo-2.5%Re-72.5% support (CeO2 modified carbon) solution 1 27.8731 g of Ni(NO3)2·6H2O was placed in a glass beaker and dissolved in 40 ml of deionized water under vigorous stirring with a magnetic stirrer without heating until completely dissolved.

[0056] solution 2 1.1500g of (NH4)6Mo7O 24 ·4H2O was placed in a glass beaker and dissolved in 25 ml of deionized water with vigorous stirring using a magnetic stirrer without heating until completely dissolved.

[0057] Solutions 1 and 2 were mixed and diluted to 100 ml with deionized water and stirred to obtain a homogenous solution.

[0058] solution 3 0.9018 g of NH4ReO4 was placed in a glass beaker and dissolved in 50 ml of deionized water under vigorous stirring with a magnetic stirrer without heating until completely dissolved.

[0059] Impregnation of the modified support with Ni-Mo mixed solution was carried out by stepwise impregnation followed by drying at 105 °C according to the incipient wetness method. After the last impregnation, the sample was calcined at 300 °C for 120 min according to the incipient wetness method and subsequently impregnated with solution 3. The thus impregnated sample was dried overnight at 105 °C and then reduced with hydrogen (5-10% H2 in N2) at 520 °C for 180 min.

[0060] The modified conductive carbon was the same as in Example 1 above.

[0061] Anode Adjustment 25 g of the above reduced catalyst was mixed with polytetrafluoroethylene (PTFE) in a weight ratio of catalyst / PTFE of 80 / 20. Mixing was carried out at room temperature using a blender for about 5 minutes.

[0062] The resulting mixture of catalyst and PTFE was placed in a rolling device to produce ribbons. The produced catalyst ribbon was placed on a nickel grid (wire diameter 0.14 mm, aperture diameter 0.4 × 0.4 mm) and pressed onto it to obtain the anode material. The ribbon was 17 cm long. 2 The anode was cut into pieces of 10 mm.

[0063] Anode Testing The anodes were tested by volt-ampere curves (VAC) on a half-cell test bench (HCTB). The volt-ampere curves (VAC) obtained from galvanostatic measurements give a good preliminary estimation of the performance of the electrodes. The galvanostatic experiments simulate the real conditions and loads on the cathode in a fuel cell.

[0064] The HCTB provides a constant thermostatically controlled circulation of 6M KOH electrolyte at 70°C. The anode is tested in a half-cell with a counter electrode and a reference electrode. The anode is a gas-liquid electrode, i.e., covered by liquid electrolyte on one side and exposed to hydrogen gas atmosphere on the other side. The half-cell has a gas chamber on the gas side of the working electrode. The HCTB also provides hydrogen flow at the desired pressure and flow rate, and the working gas (H2) can be replaced with an inert gas (N2). The VAC is intended to set constant current steps and monitor the potential of the electrode, measuring 0. <I<250mA / cm 2 The steady-state potential at each constant current step is measured and plotted against the current density to obtain the volt-ampere characteristics.

[0065] Figure 1 shows the VAC of the anode containing Re-free and Re-doped catalysts prepared as described above in Examples 1 and 2. Figure 2 shows the VAC of the anode containing Re-doped catalyst prepared as described above in Example 3.

[0066] If the anode does not respond immediately to hydrogen exposure, an external power source can be used to increase the hydrogen concentration, e.g., to 5 mA / cm 2 It should be noted that a simple electrochemical activation process can be applied in which a current of 0.1 V can be applied to a two electrode fuel cell for 30 minutes.

[0067] The anode is connected to the negative polarity and the cathode is connected to the positive polarity. To prevent over-oxidation of the cathode, which is the counter electrode, the cell voltage must be constantly monitored to ensure that it does not exceed 1.2V.

[0068] In summary, the present invention provides the following: 1. A catalyst for an anode of a fuel cell, the catalyst comprising, in at least partially reduced form, (i) nickel and (ii) molybdenum, and optionally (iii) rhenium and / or (iv) at least one transition metal different from nickel, molybdenum and rhenium, supported on (v) conductive carbon modified with one or more elements selected from lanthanides, yttrium, tin and titanium, the weight ratio of (i):((ii)+(iii)+(iv)) being at least 2:1. 2. The catalyst according to item 1, characterized in that (iii) is present. 3. The catalyst according to any one of items 1 and 2, characterized in that (iv) is present. 4. The catalyst according to item 3, wherein (iv) contains at least one of cobalt and tungsten. 5. The catalyst according to any one of items 1 to 4, wherein the lanthanide includes at least one of cerium and lanthanum. 6. The catalyst according to any one of items 1 to 5, wherein the conductive carbon is modified with cerium. 7. A catalyst according to any one of claims 1 to 6, characterized in that one or more elements modifying the conductive carbon are present at least partially as an oxide. 8. The catalyst according to any one of claims 1 to 7, wherein the one or more elements modifying the conductive carbon are present in a concentration of at least 0.5% by weight, based on the total weight of the modified conductive carbon. 9. The catalyst according to any one of items 1 to 8, wherein the catalyst contains at least 10% by weight of (i) based on the total weight of (i) to (v). 10. The catalyst according to any one of items 1 to 9, wherein the catalyst contains at least 0.5% by weight of (ii) based on the total weight of (i) to (v). 11. The catalyst according to any one of items 1 to 10, wherein the catalyst contains 5% by weight or less of (ii). 12. The catalyst according to any one of items 1 to 11, characterized in that the catalyst contains at least 0.5% by weight of (iii) based on the total weight of (i) to (v). 13. The catalyst according to any one of items 1 to 12, wherein the catalyst contains 5% by weight or less of (iii). 14. The catalyst according to any one of items 1 to 13, characterized in that the catalyst contains at least 50% by weight of (v) based on the total weight of (i) to (v). 15. The catalyst according to any one of items 1 to 14, wherein the catalyst is substantially free of Pt, Pd, Ru, Ag and Au. 16. A catalyst according to any one of the preceding claims, characterized in that it is obtained by a process comprising impregnation of component (v) with a solution of one or more compounds of nickel and molybdenum, with a solution of one or more compounds of optional rhenium and / or with one or more compounds of nickel, molybdenum and one or more compounds of a transition metal other than rhenium, followed by at least partial reduction of the metals present. 17. An anode for a fuel cell, characterized in that the anode comprises a catalyst according to any one of items 1 to 16. 18. A fuel cell, characterized in that the fuel cell comprises an anode according to item 17. 19. A process for producing a catalyst according to any one of claims 1 to 16, characterized in that the process comprises impregnating component (v) with a solution of one or more compounds of nickel and molybdenum, one or more solutions of optional rhenium compounds and / or one or more solutions of compounds of nickel, molybdenum and one or more compounds of a transition metal other than rhenium, followed by at least partial reduction of the metals present. 20. The process according to item 19, characterized in that the impregnation is carried out by the incipient wetness method. 21. The process according to any one of items 19 and 20, characterized in that before the reduction, a drying operation and optionally a calcination operation are carried out. 22. The process according to any one of claims 19 to 21, wherein the at least partial reduction is carried out using hydrogen. 23. The process according to item 22, wherein the reduction is carried out in the presence of urea. 24. An electric device, characterized in that it is electrically connected to the fuel cell according to item 18. 25. A method of powering an electrical device, the method comprising establishing an electrical connection between the device and a fuel cell according to item 18.

Claims

1. 1. A catalyst for an anode of a fuel cell, comprising, in at least partially reduced form, (i) nickel and (ii) molybdenum, and optionally (iii) rhenium and / or (iv) at least one transition metal different from nickel, molybdenum and rhenium, supported on (v) conductive carbon modified with one or more elements selected from lanthanides and yttrium, wherein the weight ratio of (i):((ii)+(iii)+(iv)) is at least 2:

1.

2. 2. The catalyst of claim 1, wherein (iii) is present.

3. 3. The catalyst according to claim 1, wherein (iv) is present.

4. 4. The catalyst of claim 3, wherein (iv) comprises at least one of cobalt and tungsten.

5. 5. The catalyst according to claim 1, wherein the lanthanide comprises at least one of cerium and lanthanum.

6. 6. The catalyst according to claim 1, wherein the conductive carbon is modified with cerium.

7. 7. A catalyst according to any one of the preceding claims, characterized in that the one or more elements modifying the conductive carbon are at least partially present as an oxide.

8. 8. The catalyst of claim 1 , wherein the one or more elements modifying the conductive carbon are present in a concentration of at least 0.5 wt. %, based on the total weight of the modified conductive carbon.

9. 9. The catalyst according to claim 1, wherein the catalyst comprises at least 10% by weight of (i), based on the total weight of (i) to (v).

10. 10. The catalyst according to claim 1, comprising at least 0.5 wt. % of (ii), based on the total weight of (i) to (v).

11. 11. A catalyst according to any one of claims 1 to 10, characterized in that the catalyst comprises up to 5% by weight of (ii).

12. 12. The catalyst of claim 1, comprising at least 0.5 wt. % of (iii), based on the total weight of (i) to (v).

13. 13. A catalyst according to any one of claims 1 to 12, characterized in that the catalyst comprises up to 5% by weight of (iii).

14. 14. The catalyst according to any one of claims 1 to 13, characterized in that the catalyst comprises at least 50 wt. % of (v), based on the total weight of (i) to (v).

15. 15. The catalyst according to claim 1, wherein the catalyst is substantially free of Pt, Pd, Ru, Ag and Au.

16. 16. An anode for a fuel cell, characterized in that the anode comprises a catalyst according to any one of claims 1 to 15.

17. 20. A fuel cell comprising an anode according to claim 16.

18. 16. A process for producing a catalyst according to any one of claims 1 to 15, characterized in that the process comprises impregnating component (v) with a solution of one or more compounds of nickel and molybdenum, with a solution of one or more compounds of optional rhenium and / or with one or more solutions of compounds of nickel, molybdenum and one or more compounds of a transition metal other than rhenium, followed by at least partial reduction of the metals present.

Citation Information

Patent Citations

  • Preparation method of hydrogenation catalyst and catalyst

    CN106423161A

  • Carbon carried Pd / oxide composite electric catalyst and preparing process thereof

    CN1719647A

  • Producing active electrode and using same in electrochemical cell

    JP1980044597A

  • Cathode electrode catalyst for fuel cell and method of manufacturing the same

    JP2003100308A

  • Catalyst layer for fuel cell, and catalyst layer-electrolyte film laminate

    JP2007273280A